2017
DOI: 10.1177/0030222816688151
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psychometrically Tested Instruments Assessing Suicide Risk in Adults

Abstract: More diverse population representation, and non-English versions of instruments, is required to improve generalizability of assessment measures. Including underrepresented groups and non-English instruments will promote culturally and linguistically sensitive instruments that may better assess suicide risk in diverse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 91 publications
(229 reference statements)
0
6
0
Order By: Relevance
“…However, few psychometric analyses have been performed across cultures. Yet, as concluded by Kreuze and Lamis (2018), devising non-English versions of instruments—along with their administration to more diverse and underrepresented populations—is crucial for improving the generalizability and sensitivity of measures for assessing suicide risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few psychometric analyses have been performed across cultures. Yet, as concluded by Kreuze and Lamis (2018), devising non-English versions of instruments—along with their administration to more diverse and underrepresented populations—is crucial for improving the generalizability and sensitivity of measures for assessing suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…Linehan et al. (1983)pioneered the development of the first inventory to assess reasons for living in adults—the Reasons for Living Inventory (RFL) (Linehan et al., 1983), which is currently one of the most used instruments and one with the strongest psychometric properties (Kreuze & Lamis, 2018). Although this measure was originally developed for adults, some authors have nevertheless used it in the adolescent population (Cole, 1989; Range, Hall, & Meyers, 1993), which entailed several limitations (Gutierrez, 2006; Osman et al., 1998; Pinto, Whisman, & Conwell, 1998; Range et al., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] There are other instruments that allow health professionals to assess suicide risk, although none specifically validated for the use by Nursing professionals in Brazil, as demonstrated in literature reviews. [13][14]…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first to assess the psychometric properties of the shortened P-RFL-OA administered across different cultures. Kreuze and Lamis (2018) suggested that developing non-English versions of suicide risk assessment tools is very important to improving their generalizability and specificity. Following the original study (Lutz et al, 2019), the data in the present study indicated the acceptable psychometric properties of the shortened P-RFL-OA in terms of internal consistency, test-retest reliability, face and content validity, convergent and divergent validity, and the known-group validity for Iranian clinical and nonclinical older adults.…”
Section: Discussionmentioning
confidence: 99%